BUDAYA ORGANISASI, PEMBERIAN INSENTIF DENGAN KOMITMEN KERJA KEPALA SEKOLAH MENENGAH NEGERI DI KOTA-KOTA DALAM PROVINSI SUMATERA BARAT - Syahril Syahril (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2015)
The study was inspired by the low of work commitments of the principal in public secondary school at the cities in West Sumatera.The purpose is to determine the organizational culture and incentives as prediction factors work's commitments of the principal. Methodology Mixed methods research approach, in the form of embedded concurrent design or a combination of uneven. Population's studies is the principle of public secondary schools in the cities in West Sumatra province, amounting to 150 people. A sample of 116 people that taken at random. The research instrument was a questionnaire and an interview guide. Data processing is performed by multiple regression analysis and thematic. Results of data processing research indicates that organizational culture and incentives either individually or collectively can be used as a factor forecasters to work commitments principals.